2018
DOI: 10.1080/2162402x.2018.1504728
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutation-associated T follicular helper cell elevation in lung adenocarcinoma

Abstract: T follicular helper cells (Tfh) play crucial roles in the development of humoral immunity. In the B cell-rich germinal center of lymphoid organs, they select for high-affinity B cells and aid in their maturation. While Tfh have known roles in B cell malignancies and have prognostic value in some epithelial cancers, their role in lung tumour initiation and development is unknown. Through immune cell deconvolution, we observed significantly increased Tfh in tumours from two independent cohorts of lung adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In patients with hepatocellular carcinoma, a reduction in circulating and/or tumorassociated Tfh cells was correlated with disease progression and reduced diseasefree survival (36). Tfh TIL were also positively correlated with tumor mutational burden in lung adenocarcinoma (37). Tfh cells in the blood and pulmonary metastasis of patients with differentiated thyroid cancer were recently shown to be higher in metastatic patients; however, these cells produced lower quantities of IL-10, IL-21 and CXCL13, suggesting reduced helper functions could participate in disease progression (38).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with hepatocellular carcinoma, a reduction in circulating and/or tumorassociated Tfh cells was correlated with disease progression and reduced diseasefree survival (36). Tfh TIL were also positively correlated with tumor mutational burden in lung adenocarcinoma (37). Tfh cells in the blood and pulmonary metastasis of patients with differentiated thyroid cancer were recently shown to be higher in metastatic patients; however, these cells produced lower quantities of IL-10, IL-21 and CXCL13, suggesting reduced helper functions could participate in disease progression (38).…”
Section: Discussionmentioning
confidence: 99%
“…Different subsets of T cells are playing different roles in immune response [42]. Follicular helper T cells play crucial roles in the development of humoral immunity [43]. Yang et al [13] estimated the immune cell-type fractions in digestive system cancer and found that follicular helper T cells were the protective factors of patients' overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…the number of mutations found in the expressed genes in tumor. The relationship between immune cells and somatic mutation load has been reported 37 . Currently, immunotherapy such as PD-L1, PD-1 antagonists and Chimeric antigen receptor T cell (CAR-T) are heavily investigated in multiple cancers including medulloblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, immunotherapy such as PD-L1, PD-1 antagonists and Chimeric antigen receptor T cell (CAR-T) are heavily investigated in multiple cancers including medulloblastoma. All the immunotherapies are based on the hypothesis that tumors harbor neoantigens recognizable by the human immunological system 37 . A higher mutation burden may result in more recognizable neoantigens, which is in agreement with our data.…”
Section: Discussionmentioning
confidence: 99%